Hubungan antara Riwayat status Imunisasi dan ASI Eksklusif terhadap Kejadian Stunting pada Balita - Yulianto, Sofi; Fauziyah J., Luluk (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Background: Stunting is a condition of failure to grow in children under five as a result of chronic malnutrition, especially in the first 1000 days of life (HPK), so that the child is too short for his age From the prevalence data of stunting in toddlers collected by WHO, Indonesia is included in the third country with the highest prevalence in the Southeast Asia region / South-East Asia Regional (SEAR). Bangkalan Regency is recorded as the area with the highest prevalence of stunting toddlers in East Java. Namely reaching 26.8%. Objective: To determine the relationship between exclusive breastfeeding history and immunization history and stunting incidence in Tragah District. Methods: A cross-sectional study design with a population of all toddlers aged 12-59 months with a sample of 78 people selected by proportional sampling. The data collection of this study uses a questionnaire. The data were analyzed with univariate analysis to obtain an overview of the frequency distribution, bivariate analysis with chi-squre test to obtain the relationship between two variabes. Results: Based on the results of the incomplete Immunization Status analysis with a very short stunting incidence of 22 (40%). The results of the Chi Square statistical test obtained a P Value (0.000) and almost half of the breast milk was not exclusive with a very short stunting incidence of 22 (40.7%). The results of the Chi Square statistical test obtained a P Value (0.000) with a significance level of α(0.05) risk factors for stunting. Conclusion: There is a relationship between Immunization Status and Stunting Incidence in the Working Area of the Tragah Health Center of BangkalaN Regency. There is a relationship between Exclusive Breastfeeding and Stunting Incidence in the Working Area of the Tragah Health Center, Tragah District, Bangkalan Regency